(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2012)
Antimycotic clotrimazole (CTZ) has demonstrated remarkable activity against Plasmodium falciparum in vitro and in vivo. Hemoglobin degradation by Plasmodium parasites makes amino acids available for protein synthesis, inducing oxidative stress in infected cells and producing free heme. These events represent biochemical targets for potential antimalarials. In this study, we have tested the ability of CTZ to modify the oxidative status in Plasmodium berghei-infected erythrocytes. After hemolysis, activities of superoxide dismutase (SOD), catalase (CAT), glutathione cycle and NADPH+H+-producing dehydrogenases were investigated using UV-visible spectrophotometry. Thiobarbituric acid reactive substances (TBARS) were evaluated as a marker of lipid damage. Results showed that CTZ significantly decreased the overall activity of 6-phosphagluconate dehydrogenase (6PGD) compared to infected and non-treated cells; consequently, the glutathione cycle was inhibited, leaving the parasite vulnerable to the oxidative stress originating from hemoglobin degradation. As a compensatory response, CTZ prevented some loss of SOD and CAT activities in infected cells. The infection triggered lipid peroxidation in erythrocytes, which was decreased by CTZ. These results suggest the presence of a redox unbalance in cells treated with CTZ, discussing a possible effect of this compound disturbing the oxidative status in a Plasmodium berghei-infection.